Problematisierung statt Optimierung? Verhandlungen einer klärungsbedürftigen Beziehung in der Erwachsenenbildung - Ebner von Eschenbach, Malte; Kondratjuk, Maria; Stimm, Maria; Trumann, Jana; Wagner, Farina (Debatte Sonderheft, 2023)
The first special issue of the journal "Debatte" brings together contributions and replicas on adult education that put a change of perspective up for discussion: While optimisation is often used as a solution to problems in educational science, the special issue focuses on problematisation. For optimisation implicitly presupposes an already defined goal, whereas problematisation allows an openness to its object. The adjunctive implications unfold along the following empirical fields: migration research, higher education, science communication and continuing education counselling.